Kemampuan Pasta Gigi yang Mengandung Ekstrak Biji Kopi Robusta (Coffea canephora) dalam Menghambat Pertumbuhan Bakteri Fusobacterium nucleatum - Vindy. W, Imaniar Fitriatasya; Pujiastuti, Peni; Praharani, Depi (UPT Percetakan dan Penerbitan Universitas Jember, 2025)
Fusobacterium nucleatum is a gram-negative obligate anaerobic bacterium that is most dominantly found in the oral cavity and plays an important role in periodontitis pathology. Periodontitis can be prevented by controlling plaque, namely, brushing teeth. Therefore, toothpaste needs to be optimized by adding an antibacterial substance. The robusta coffee (Coffea canephora) contains caffeine, phenols, trigonelline, chlorogenic acid, saponins, tannins, and triterpenoids, which have proven to be antibacterial. This study aimed to assess the ability of toothpaste containing robusta coffee bean extract to inhibit the growth of F. nucleatum. Robusta coffee beans were extracted using the maceration method and formulated into toothpaste with concentrations of 12.5%, 25%, and 50%. Antibacterial tests were carried out by the well diffusion method on MHA media that had been inoculated with F. nucleatum and the measured the diameter of the inhibition zone. The result showed that there was a significant difference in the inhibition zone diameter between the group positive control, the negative control, and toothpaste containing robusta coffee bean extract 12.5%, 25%, and 50%. The largest inhibition zone formed consecutively was in toothpaste containing robusta coffee bean extract 50%, 25%, and 12,5%. It can be concluded that toothpaste containing robusta coffee bean extract with concentrations of 12.5%, 25%, and 50% can inhibit the growth of F. nucleatum.